Evidence for the intimate relationship between vesicle budding from the ER and the unfolded protein response - Sato, Miyuki; Sato, Ken; Nakano, Akihiko (Biochemical and biophysical research communications, 2002)
Yeast Saccharomyces cerevisiae Sec12p, an ER membrane protein, carries out an essential function as the guanine nucleotide exchange factor of the small GTPase Sar1p. Sar1p-GTP is pivotal for the assembly of a coat protein complex, COPII, on the ER membrane, and thus Sec12p can be regarded as the initiator of vesicle budding from the ER. In an effort to identify genes that positively regulate Sec12p, we isolated IRE1 as a novel multicopy suppressor of the temperature-sensitive sec12-4 mutant. IRE1 encodes a transmembrane kinase/nuclease, which controls the unfolded protein response (UPR) to induce transcription of ER chaperones under stress conditions. The constitutive activation of the UPR by overexpression of either IRE1 or active mutant HAC1, a transcription factor responsible for the UPR, suppresses sec12-4. Interestingly, overproduction of some cargo proteins also results in suppression of sec12-4 through the activation of the UPR. The overexpression of IRE1 suppresses the sec mutants defective in vesicle budding from the ER but not others, highlighting a close relationship between the ER exit and the UPR.